A novel method to improve heating uniformity in mid-high moisture potato starch with radio frequency assisted treatment. (August 2017) - Zhu, Hankun; Li, Dong; Li, Shujun; Wang, Shaojin
Abstract: An alternative method to improve treatment efficiency for industrial applications of mid-high moisture potato starch was explored based on radio frequency (RF) heating, but the large cold spot area during RF treatment was the biggest obstacle for technology development. The purpose of this study was to develop a new method to reduce the cold spot area and improve RF heating uniformity for mid-high moisture potato starch by modifying the electromagnetic field distribution in the sample with a Electromagnetic Wave Conductor (EWC). The simulation model of RF heating was established to study the temperature distribution using commercial COMSOL software. Dielectric properties of potato starch with moisture content of 31.55% w.b. were measured for computer simulation, and the associated RF experiments were conducted as the validation of the EWC method. The results showed that the parameters of EWC (width and height) had a positive correlation with the RF heating uniformity. The improved target uniformity index (TUI) and the decreased heating time indicated significant effects of EWC. Finally, optimizing EWC parameter equations were developed and could be used for improving RF heating uniformity in future applications. Highlights: Electromagnetic Wave Conductor (EWC) was introduced to improve RF heating uniformity. Dielectric properties of potato starch were determined and used in simulation. Validated simulation model was developed to optimize EWC parameters. Optimized EWC parameter equations were provided for practical applications.